2016
DOI: 10.1681/asn.2015050508
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synthesis of Liver Erythropoietin with CKD

Abstract: Anemia of CKD seems to be related to impaired production of renal erythropoietin (Epo). The glycosylation pattern of Epo depends on the synthesizing cell and thus, can indicate its origin. We hypothesized that synthesis of Epo from nonkidney cells increases to compensate for insufficient renal Epo production during CKD. We determined plasma Epo levels and Epo glycosylation patterns in 33 patients with CKD before undergoing dialysis and nine patients with CKD undergoing dialysis. We compared these values with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 18 publications
1
34
1
1
Order By: Relevance
“…Therefore, we think that most part of EPO induced by TP0463518 is produced by liver. In HD patients, baseline PMI values were higher than those in peripheral blood and similar to umbilical cord blood in consistent with results of a previous report [12], which suggests that some of EPO in HD patients originates in the liver to compensate for insufficient renal EPO production. After TP0463518 administration in HD patients, PMI values were even higher than umbilical cord values (84.4 ± 3.5 vs. 57.2 ± 5.5%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, we think that most part of EPO induced by TP0463518 is produced by liver. In HD patients, baseline PMI values were higher than those in peripheral blood and similar to umbilical cord blood in consistent with results of a previous report [12], which suggests that some of EPO in HD patients originates in the liver to compensate for insufficient renal EPO production. After TP0463518 administration in HD patients, PMI values were even higher than umbilical cord values (84.4 ± 3.5 vs. 57.2 ± 5.5%).…”
Section: Discussionsupporting
confidence: 91%
“…4). In CKD study, PMI value in ND patients was similar to that in peripheral blood and lower than umbilical cord blood, which is different from the result in de Seigneux et al [12]. Variation of PMI value may be large between samples and assays, but baseline PMI value greatly increased after TP0463518 administration in ND patients.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…It was also reported that patients with anemia can switch EPO production from the kidney to the liver [30,31], as can be shown by glycoform analysis of EPO. Indeed, the posttranslational EPO glycosylation is specific of the synthesizing cells, giving rise to different EPO glycoforms that can be used to localize EPO synthesis [30,32].…”
Section: Introductionmentioning
confidence: 80%
“…Anemia is common in patients with ESRD [27], due to impaired production of renal erythropoietin [28].…”
Section: Discussionmentioning
confidence: 99%